2019
DOI: 10.1186/s12887-019-1697-y
|View full text |Cite
|
Sign up to set email alerts
|

Physicians advice, parental practice and adherence to doctor’s advice: an original survey on infant feeding

Abstract: Background: Despite several years of guidance on infant feeding, there has been only a slight change in consumer compliance. Therefore, this study aimed to analyse parents feeding practices, explore physicians’ advice about infant feeding and subsequent parent’s adherence to advice. Methods A multicentric cross-sectional qualitative and descriptive self-report online study was conducted in volunteers to participate in the study. Results Fifty-four physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
4
10
0
2
Order By: Relevance
“…Soft pureed vegetables were regarded as the most appropriate foods to start complementary feeding, as well as the most important food during the first meals. Similar results were reported by a recent study conducted in France (43) . Interestingly, the variety of vegetables mentioned by the paediatricians was limited and mainly stressed pumpkin, potatoes and carrots.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Soft pureed vegetables were regarded as the most appropriate foods to start complementary feeding, as well as the most important food during the first meals. Similar results were reported by a recent study conducted in France (43) . Interestingly, the variety of vegetables mentioned by the paediatricians was limited and mainly stressed pumpkin, potatoes and carrots.…”
Section: Discussionsupporting
confidence: 92%
“…This points out that traditional approaches to complementary feeding are still predominant in the recommendations of Uruguayan paediatricians, whereas baby-led weaning still has a marginal role. Similar results have been reported in previous studies conducted in different countries (43,(47)(48)(49) . This result is probably related to the fact that baby-led weaning has not been introduced as an alternative recommended practice in the national and international guidelines on complementary feeding (5,37,38) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study did not reveal important differences between the new recommendations and the advising practices of professionals (especially HCPs) but still pointed out particular advice given by professionals that could be updated and improved in light of the new recommendations, in particular with regard to the introduction of allergens and of all types of food between four to six months of age. Our results are in line with those of a study conducted in France in 2016, in which the interviewed general practitioners and pediatricians reported giving advice on child feeding in line with recommendations (55). For instance, in this study, professionals acknowledged that the right age for introducing complementary food was between four and six months of age and gave the appropriate advice to parents in 85.2% of cases.…”
Section: Discussionsupporting
confidence: 90%
“…Another contributing factor of the diverging views might be the varying levels of health professionals' knowledge of current evidence on complementary feeding. A survey by Chouraqui et al revealed a discordance between parents' statements of the infant feeding advice received and the statements of paediatricians who offered this advice (82) . Hence, an assessment of healthcare staff's knowledge of current complementary feeding guidelines and their perceived barriers to an effective nutritional education is required to complement parental perspectives and give directions for improved access to feeding recommendations.…”
Section: Factors In Relation To Both Age Of Introduction and Type Of Solid Foodsmentioning
confidence: 99%